Ecological balance of Iron ore mines land in Chhattisgarh by using vesicular arbuscular mycorrhiza fungi. - Sahu, Pradeep Kumar; Chatterjee, Tanushree (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> The State of Chhattisgarh is situated in the Mid Eastern India, bounded between North latitude 170 46’ to 240 06’ and East Longitude 800 15’ to 84025’ and the states is geologically one of the most important terrains in the Indian shield comprising of litho logical sequence ranging in age from Archaean to Recent. Bountiful nature has bestowed Chhattisgarh with vast reserves of all important minerals. Chhattisgarh state has rich sources of mineral resource especially iron and coal. Open cast mining is the dominant form of mining. The immediate effect of open cast mining is the removal of soil and vegetation cover. The extent of damage depends on location of mining site, scale of operation, mining methods, degree of mechanization etc. The effects of mining activity as well as mining waste causes such as soil erosion, air and water pollution, toxicity, geo-environmental disasters, loss of biodiversity, and ultimately loss of economic wealth. This research paper presenting the how Vesicular Arbuscular Mycorrhiza fungi used for ecological balances. VAM fungi are types of endomycorrhizae and used as biofertilizer for revegetation of mining destroyed sites especially iron ore mines in Chhattisgarh. Mycorrhizae associate plants shows more root and shoot height, fresh and dry biomass weight, high content of soluble protein and low rate of mortality when planting in actual mining sites. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>